Language development and language impairment a problem-based introduction - Fletcher, Paul 1943-; O'Toole, Ciara (Chichester, West Sussex, [England] John Wiley & Sons, Inc., 2016)
"Language Development and Language Impairment offers a problem-based introduction to the assessment and treatment of a wide variety of childhood language developmental disorders. Focuses for the most part on the pre-school years, the period during which the foundations for language development are laid Uses a problem-based approach, designed to motivate students to find the information they need to identify and explore learning issues that a particular speech or language issue raises Examines the development of a child's phonological system, the growth of vocabulary, the development of grammar, and issues related to conversational and narrative competence Integrates information on typical and atypical language development "-- Provided by publisher.
Part 1: Overview 1.1 The effects of pre-school language impairment 1.2 The ambient language 1.3 Typical language development 1.4 Atypical language development Part 2: The first year of life 2.1 Introduction 2.2 Social development and language learning 2.3 Cognitive development and language development 2.4 Speech production in infancy 2.5 Speech perception in infancy 2.6 Further Problems Part 3: Sounds 3.1 The learning task 3.2 The role of perception 3.3 The production of vowels 3.4 The production of consonants 3.5 Further Problems Part 4: Words 4.1 Early vocabulary development 4.2 Learning to label: first steps 4.3 Building a lexicon 4.4 Lexical growth and individual differences 4.5 Beyond nouns 4.6 A bridge to syntax 4.7 Further Problems Part 5: Combining words 5.1 Introduction 5.2 Transcribing and analyzing language samples 5.3 Verb forms: auxiliaries and inflections 5.4 Interrogatives: asking questions 5.5 Complex sentences 5.6 Further Problems Part 6: Beyond the sentence 6.1 Introduction 6.2 Early pragmatic competence 6.3 Discourse skills 1: Conversation 6.4 Discourse skills 2: Telling stories 6.5 Presupposition 6.6 Pragmatic language difficulties 6.7 Further problems. Appendix 1: IPA consonant and vowel charts Appendix 2: Reliability and validity Appendix 3: Sensitivity and specificity Appendix 4: Techniques for exploring speech perception in infants Appendix 5: Grammatical analysis using the LARSP profile.
Includes bibliographical references and index.
Keywords: Language disorders in children